WAYS TO IMPROVE THE MECHANISM FOR EVALUATING INNOVATIVE TRADE SERVICES - Nizomova Ruhsora Akramovna (World Scientific Research Journal, 2025)
Annotation. This study examines the importance of innovative trade services, the analysis of existing mechanisms for their evaluation, and the necessity for their improvement. It demonstrates scientific approaches, modern evaluation methods, and the role of digital technologies in achieving efficiency in the implementation and assessment of innovations in the trade sector. Furthermore, it analyzes international experience and develops proposals and recommendations that are suitable for local conditions. The results of this research contribute to the formation of an effective model for evaluating innovative services.